The long-term curative effect analysis of trans-articular plate combined with Kirschner wires in the treatment of fracture-dislocation of the fifth carpometacarpal joint - Zhou, Ying; Wu, Ye; Huang, Yinjun; Xie, Renguo; Gu, Song (Frontiers in Surgery, 2023)
Abstract Purpose To evaluate the long-term curative effect analysis of trans-articular plate combined with Kirschner wires in the treatment of fracture-dislocation of the fifth carpometacarpal joint. Methods From July 2016 to September 2021, 21 patients with fracture-dislocation of the fifth carpometacarpal joint were treated with trans-articular plate combined with Kirschner wires internal fixation. Each patient’s gender, age, dominant hand, injured hand, trauma mechanism, the time between injury and surgery, the range of motion of the bilateral wrist in flexion, extension, radial deviation and ulnar deviation, grip strength of each side, the time of return to work, and follow-up time were recorded. The QDASH score and Cooney wrist function score were used to evaluate the postoperative function. The VAS system was used to evaluate postoperative pain. Results The follow-up time was 37.0±19.0 months and the time between injury and surgery was 1.3±0.5 days. In the injured side and the contralateral side, the range of motion of the wrist flexion were 58.3±4.0° and 60.5±3.1° , the range of motion of the wrist radial deviation were 25.7±3.3° and 26.9±2.9° , the range of motion of the wrist ulnar deviation were 28.1±3.7° and 29.5±3.1° respectively with no significant difference. The range of motion of the wrist extension (54.0±3.4°) in the injured side was smaller than that in the contralateral side (56.7±3.7°) with significant difference. The grip strength of the injured side and the contralateral side were 96.1±9.5 LB and 100.7±9.7LB respectively with no significant difference. The QDASH score was 3.8±1.8, Cooney wrist function score was 94.5±4.2, VAS score was 1.0±0.8 and the time of return to work was 5.1±0.9 weeks. In the 21 cases, no postoperative complications such as incision infection, failure of internal fixation, fracture nonunion or fracture malunion occurred. Conclusion The method of trans-articular plate combined with Kirschner wires is one of the alternative treatments for the fracture-dislocation of the fifth carpometacarpal joint. The long-term follow-up results were satisfactory.